Psychology applied to teaching : study guide - Biehler, Robert F. (Robert Frederick), 1927-; Snowman, Jack. (Boston : Houghton Mifflin, 1997)
Applying psychology to teaching. Stage theories of development. Age-level characteristics. Understanding cultural diversity. Assessing student variability. Dealing with student variability. Devising and using objectives. Behavioral and social learning theories. Information-processing theory...
Keywords: Education; Educational psychology; Educational psychology